Recent insights in atopic dermatitis pathogenesis, treatment, and disease impact - Madison Nguyen; Adrian Pona; Sree S Kolli; Steven R Feldman; Lindsay C Strowd (Wolters Kluwer Medknow Publications, 2019)
Atopic dermatitis (AD) is the most common inflammatory skin condition impacting patient quality of life. Although AD is widely studied, investigators have explored recent advancements in AD pathogenesis, treatment, and disease impact. Therefore, this article summarizes recent advancements in AD pathogenesis, treatments, and disease impact on patient quality of life. A PubMed search was conducted using the keywords: "atopic dermatitis AND pathogenesis," "atopic dermatitis AND microbiota," "atopic dermatitis AND dupilumab," "atopic dermatitis AND JAK$ inhibitors," and "atopic dermatitis AND quality of life." Epidermal barrier dysfunction and immune dysregulation play a key role in the pathogenesis of AD. Although most AD patients express a filaggrin mutation, such mutation alone does not predict disease severity. Immune dysregulation is characterized by T-helper-2 responses in acute AD and Th1 responses in chronic AD. Skin microbiota abnormalities and sweat exacerbate symptomatology. Dupilumab targets the interleukin (IL)-4Rα and is the only Food and Drug Administration-approved biologic that effectively treats AD. Newer alternative agents for AD treatment include IL-12 and IL-23 inhibitors, IL-31R inhibitors, and JAK inhibitors. AD patients have increased anxiety, depression, and sleep disorders (P < 0.001) and skin pain (P= 0.02) compared to control. AD is influenced by the epidermis, immune system, genetics, microbiota, sweat, and environment. AD has lasting impacts on patients' mental and physical health. Dupilumab is an effective biologic for treating the condition.